Arte em Exposição: Drummond’s poetry as a critical perspective on art - Silva, Rodrigo dos Santos Dantas da; Ribeiro, Roney Jesus (Revista do Colóquio, 2026)
The article analyzes Arte em Exposição, by Carlos Drummond de Andrade, highlighting poetry as a singular form of art criticism. Its objective is to investigate how Drummondian poetic practice functions as an instrument for the interpretation and recreation of the visual arts. The methodology is based on the analysis of poems inspired by paintings and sculptures, articulated with theoretical frameworks from aesthetic criticism and intersemiotic translation. The study demonstrates how word and image intertwine in the construction of meaning, expanding the reader’s aesthetic experience. By privileging a sensitive and reflective approach, the article reveals the power of poetry as a critical language capable of challenging historical and visual discourses. In this context, it emphasizes the ethical dimension of Drummond’s writing, which transforms artistic contemplation into a reflection on the human condition.